Direito ao esquecimento: uma análise constitucional na sociedade de informação - Gerdulo, Fábio Paiva (2016)
This work aims primarily to demonstrate the development of the sui generis institution of the "Right to Oblivion". To get to the heart of the matter, it develops the theme from the show what it is called the "information society" as well as her relationship with the greater need to use the "Right to Oblivion" nowadays. Moreover, the Constitutional principles that give foundation to use the institute, were explained, namely the Principle of Human Dignity and the Right to Privacy, Intimacy and Honor. This tune was also explored the Freedom of Expression Principle, which is true obstacle, especially in the United States, the use of the "Right to Oblivion". A very important point mentioned in the job was, that the information that individuals provide by using technology might come in the future to influence directly their relationship with society. In this moment, the "Right to Oblivion" can be an important short tool so that this information would be prohibited to be used. In the same way, it was carried out in-depth study of the doctrine and the case law of the "Right to Oblivion" in Europe and the United States, emphasizing especially the most important cases that ultimately direct as that law was to be applied by the courts of the place. Finally, the study sought to study how this institute novel appeared in Brazilian lands, their development before the doctrine and the judiciary, the key cases to the issue of development in the country, as is currently being implemented and which provisions have been used for your application or not on the case